The complex care of a torture survivor in the United States: The case of “Joshua” - Berthold, S. Megan; Polatin, Peter; Mollica, Richard; Higson-Smith, Craig; Streets, Federick J.; Kelly, Caitrin M.; Lavelle, James (Torture Journal, 2020)
Introduction: Torture is an assault on the physical and mental health of an individual, impacting the lives of survivors and their families.The survivor’s interpersonal relationships, social life, and vocational functioning may be affected, and spiritual and other existential questions may intrude. Cultural and historical context will shape the meaning of torture experiences and the aftermath. To effectively treat torture survivors, providers must understand and address these factors. The Complex Care Model (CCM) aims to transform daily care for those with chronic illnesses and improve health outcomes through effective team care. Methods: We conduct a literature review of the CCM and present an adapted Complex Care Approach (CCA) that draws on the Harvard Program in RefugeeTrauma’s five-domain model covering the Trauma Story, Bio-medical, Psychological, Social, and Spiritual domains.We apply the CCA to the case of “Joshua,” a former tortured child soldier, and discuss the diagnosis and treatment across the five domains of care. Findings: The CCA is described as an effective approach for working with torture survivors. We articulate how a CCA can be adapted to the unique historical and cultural contexts experienced by torture survivors and how its five domains serve to integrate the approach to diagnosis and treatment. The benefits of communication and coordination of care among treatment providers is emphasized. Discussion / Conclusions: Torture survivors’ needs are well suited to the application of a CCA delivered by a team of providers who effectively communicate and integrate care holistically across all domains of the survivor’s life.